Effect of sowing date on Striga infestation and yield of sorghum (Sorghum bicolor [L.] Moench) cultivars in the Sudan savanna of northeast Nigeria - Ekeleme, F.; Kamara, A.Y.; Omoigui, L.O.; Chikoye, David; Dugje, I.Y.; Tegbaru, A. (Academic Journals, 2011)
Striga hermonthica is a serious biotic constraint to sorghum production in the dry savannas of subSaharan Africa but the use of improved cultivars and appropriate planting dates may help to control the weed. A two year trial was conducted to evaluate the effect of sowing dates on four sorghum cultivars (improved: ICSV111, ICSV400, KSV8, and landrace: HANUNGIWA) under natural infestation with S. hermonthica in northeast Nigeria. In early sowing, the number of emerged Striga plants was twice the number found when sowing was delayed by 21 or 28 days. ICSV111 and ICSV400 had 25 to 110% fewer Striga shoots than KSV8 and HANUNGIWA. Although Striga infestation was significantly more on KSV8 this cultivar had a higher yield than the others except for ICSV111 which had the highest grain yield. KSV8 and HANUNGIWA produced significantly more grain when sown in the first week of July. The yields of ICSV111 and ICS400 increased substantially when sown in the fourth week of July. Farmers in the zone would maximize sorghum yield if improved cultivars are planted at the appropriate dates in Striga infested fields.